The Local Government Budget Resilience: Anticipatory, Coping, and Vulnerability Indexes - Indriani, Ika Kurnia; Agus Widodo; Anik Cahyowati (Future Science, 2024)
The primary determinant for managing the financial distribution consequences of the COVID-19 pandemic is the resilience of the local budget. Having a substantial budget will facilitate the implementation of strategic programmes by the municipal administration during the COVID-19 epidemic, while also ensuring the maintenance of regional economic growth. The budget capability evaluation attempts to evaluate the proficiency of municipal governments in Indonesia in managing the APBD. The evaluation of budget resilience employs a descriptive quantitative methodology that encompasses three dimensions: anticipatory capacity, coping capacities, and vulnerability. The evaluation employed secondary data through the process of archive analysis. The assessment results indicated that the municipalities of Mataram, Tidore, Batam, and Sabang achieved the highest budget resilience index. The government with the highest ranking possesses the capacity to effectively manage unanticipated issues such as the COVID-19 pandemic. However, the municipalities of Bengkulu, Bontang, and Tegal showed the lowest budget capacity index. The local government with the lowest index must enhance the management system of APBD to optimise its response to the economic consequences afterwards the COVID-19 pandemic.